2020
DOI: 10.11648/j.ajcbm.20200402.12
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Problems of the Public Building Maintenance Works with Special Reference to Nepal

Abstract: The study was conducted during the period from the month of March to April 2020. Published literatures such as thesis, paper, manuals, reports, and database were collected from different sources and studied thoroughly. The conclusions were drawn on the basis of the studied materials. The study found that the public buildings of any nation are too valuable assets and maintaining them at regular functional state is becoming challenging job for developing countries like Nepal. The most significant building mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…From the responses obtained, it was concluded that although the bioengineering technique had been beneficial to solve the problems related to landslide and soil erosion, the lack of preparation, design, proper implementation, maintenance, monitoring, evaluation, and other relevant factors had caused the slope and road to revert back to its deteriorating state. According to (Chandra Dahal & Raj Dahal, 2020), poor preparation and maintenance culture are the major problems that affect the projects like the one in this research. The problems in the proper implementation of the bioengineering technique, problems in the transportation of raw materials, problems in the storage of raw materials, lack of community participation, political issues, lack of mobilization of manpower, lack of proper selection of plant species for bioengineering and lack of seedbed for fertilization caused a ruckus during the construction activities.…”
Section: Discussionmentioning
confidence: 99%
“…From the responses obtained, it was concluded that although the bioengineering technique had been beneficial to solve the problems related to landslide and soil erosion, the lack of preparation, design, proper implementation, maintenance, monitoring, evaluation, and other relevant factors had caused the slope and road to revert back to its deteriorating state. According to (Chandra Dahal & Raj Dahal, 2020), poor preparation and maintenance culture are the major problems that affect the projects like the one in this research. The problems in the proper implementation of the bioengineering technique, problems in the transportation of raw materials, problems in the storage of raw materials, lack of community participation, political issues, lack of mobilization of manpower, lack of proper selection of plant species for bioengineering and lack of seedbed for fertilization caused a ruckus during the construction activities.…”
Section: Discussionmentioning
confidence: 99%
“…From the responses obtained, it was concluded that although the bioengineering technique had been beneficial to solve the problems related to landslide and soil erosion, the lack of preparation, design, proper implementation, maintenance, monitoring, evaluation, and other relevant factors had caused the slope and road to revert-back to its deteriorating state. According to [14], the poor preparation and maintenance culture are the major problems that affect the projects like the one in this research. The problems in proper implementation of the bioengineering technique, problems in transportation of raw materials, problems in storage of raw materials, lack of community participation, political issues, lack of mobilization of manpower, lack of proper selection of plant species for bioengineering, and lack of seedbed for fertilization caused ruckus during the construction activities.…”
Section: Discussionmentioning
confidence: 99%
“…In buildings, replacements are made wherever possible. It is unavoidable since various materials deteriorate at different rates due to service circumstances [33]. A lot of replacement work is caused more by deterioration of appearance than by actual material or constituent failure [34].…”
Section: Ii1 Implementation Of Maintenance Practices In Shopping Mallsmentioning
confidence: 99%
“…Building deterioration mainly depends on the type of building and the maintenance practices in place. According to [33], the main reasons for deterioration include the age of the building, natural disasters, ground settlement, deficiencies in design, poor construction supervision, the use of inferior materials, and poor workmanship. Similar studies from [52] showed that improper maintenance, inadequate design, poor workmanship, and low-quality materials are also major reasons for deterioration.…”
Section: Ii3 Causative Factors Contributing To the Deterioration Of S...mentioning
confidence: 99%